Transformasi Mitos Cadu ka Haji: Antara Tradisi Lokal dan Ajaran Islam di Masyarakat Cipaku, Sumedang - Maulana, Ilman; Hernawan, Wawan; Halim, Ilim Abdul (JENTRE, 2025)
This study aims to describe the continuity and role of this myth in the religious life of the local community, as well as to understand how this myth intertwines with the Islamic teachings they adhere to. This study uses an anthropological approach and qualitative research through literature review, participant observation, and in-depth interviews with community leaders. The analysis is conducted using Claude Lévi-Strauss's structuralism theory, which views myth as a cultural mechanism for managing the fundamental contradictions of human life. The results show that the myth of "cadu ka haji" serves as an interpretive tool in understanding socio-spiritual phenomena and serves as a bridge between local traditions and religious teachings. The Cipaku community has developed a unique way of practicing religion, where faith, myth, and ancestral values synergize in daily practice. The implications of these findings emphasize the importance of a cultural approach in Islamic propagation and the preservation of local wisdom. The originality of this study lies in revealing the syncretic dynamics between Islam and local Sundanese culture, which have not been widely explored in previous academic studies.